Rewolucja brabancka w latach 1789-1790 w świetle relacji „Gazety Warszawskiej” i „Pamiętnika Politycznego i Historycznego” - Paszyn, Maciej (Acta Universitatis Lodziensis. Folia Historica, 2001)
This artical is introduce how two polish newspapers have Brabant Revolution in 1789-1790 describe. It was „Gazeta Warszawska” edited by ex-jesuit Stefan Luskina and „Pamiętnik Polityczny i Historyczny” edited by Piotr Świtkowski ex-jezuit too. Stefan Luskina was conserwatist, adherent by Catarina II. Świtkowski was fisiocrat and democrat. Both of newspappers noticed reason rebel of Brabant. When „Gazeta Warszawska” informs only about the event „Pamiętnik” has ambitions to comments them. The reforms of Joseph II in 1780-1789 changed the Habsburg Empire. The absolute rules of Joseph II meet resistance of people of Belgium. In 1787 closed Academy of Louvin it was a reason of disturbances. The rebel was muffled by austrian government. In July 1789 emperor was cancel prerogative caled Jeuyese Entree. In October was started rebel in Brabant. Them leader was Henrijk van der Noot. Świtkowski and Luskina have describe figthing Belgian forces with austrian army. In January 1790 was published conservatiwe constitution of Belgium. Prime minister was Pierre van Eupen colaborator of Brabant leader Henrijk van der Noot. Comander in chief belgian voluntary army was general Jean Andre van der Meersch. In may 1790 comander in chief austrian army have been genera] Bender. „Gazeta Warszawska” and „Pamiętnik Polityczny i Historyczny” have describe reaction of Europa of Brabant Revolution. The attitude both of editors was considerly different. Świtkowski thinks the rebel is justifiable. Luskina treat their like as rebeliant. Both of them are oponents to leader of rebel Henrijk van der Noot. „Gazeta Warszawska” and „Pamiętnik Polityczny i Historyczny” exactly describe cours and fall the revolution in Brabant 2th December 1790.